Providing formative assessment to students solving multipath engineering problems with complex arrangements of interacting parts: an intelligent tutor approach. Issue 8 (16th November 2016) - Steif, Paul S.; Fu, Luoting; Kara, Levent Burak
Abstract : Problems faced by engineering students involve multiple pathways to solution. Students rarely receive effective formative feedback on handwritten homework. This paper examines the potential for computer-based formative assessment of student solutions to multipath engineering problems. In particular, an intelligent tutor approach is adopted and tested out on problems of truss analysis, studied in engineering statics. With a cognitive model for solving the class of problems, the tutor allows the student wide latitude in solution steps, while maintaining sufficient constraints for judging the solution and offering feedback. Proper selection of judging points prevents interference with productive student work, while avoiding accumulated errors. To monitor student learning, efforts to apply distinct skills were extracted on the fly from student work. Using statistical methods developed for intelligent tutoring systems, metrics of the effectiveness of the feedback and areas for further improvements were gleaned from error rates in successive opportunities to apply distinct skills.